Formas de pensar, regular y ocupar el borde metropolitano : Buenos Aires: 1972, 1992 y 2012 - López Goyburu, Patricia (2019)
The study of the metropolitan edge of Buenos Aires, in the last four decades, shows us that this territory is a sum of processes, in which some, which are seen as new, have started some time ago and others, previous, remain hidden. So, the metropolitan edge cannot be explained from a unitary view, but as a result of various spatial transformations, thus overcoming the debate on dichotomy or continuity field-city. On the setracks, the thesis aims to know some of the changing social processes of the metropolitan edge, how it has been thought, regulated and occupied. The analysis has allowed us to recognize sectors, such as Fatima, where the location of new generation artifacts responds, in addition to the private initiative, to the vision of the local government that sees this territory as one where to host growth, relying on the good accessibility, the availability of empty lands and some industrial development policies raised in the seventies. On the other hand, there are sectors, such as Mariano Acosta, where the completion of the urban area developed previous to the approval of the Decree-Law 8912 continues and there are no illegal occupations of idle land, product, to a large extent, of state intervention and the conditions of location and availability of service infrastructure. Contrary, we find sectors, such as El Peligro, where, despite the fact that the local government introduces, through regulations, the possibility of development of gated communities in "non-urban areas" and that there is good accessibility, immigrant producers and agricultural policies generate conditions for horticultural and floricultural uses are consolidated and intensified, resisting the advance of the urban space.